The Students’ Techniques In Translating Swear Words In The Novel Fight Club (1996) by Chuck Palahniuk - Raesa Savelia; Havid Ardi (Universitas Negeri Padang, 2022)
The purpose of this research is to find out the translation techniques used by English department students in translate swear words in the Fight Club novel. This is descriptive qualitative research. Students from the translation class were chosen for this study using a cluster random sampling technique. Techniques for collecting data include translation tests. Translation technique was classified based on Molina and Albir theory. The result of this research indicate that students’ techniques in translating swear words in novel were literal translation, adaptation, discursive creation, reduction, borrowing, established equivalent, explicitation, description, modulation, and substitution. This finding is aplies that swear words is best translated in established equivalent technique.